1981
DOI: 10.1139/y81-037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mineralocorticoids on collecting duct hydrogen ion secretion in the rabbit

Abstract: The purpose of this study was to elucidate the mechanism whereby a potassium infusion led to an elevation in the urine minus blood (ohm-B) PCO2 difference in alkaline urine of the rabbit. Rabbits given 9alpha-fluorohydrocortisone 16 h prior to study had a significantly high olm-B PCO2 than control rabbits. However, the ohm-B PCO2 was increased further after potassium infusion. These results suggest that the increased collecting duct hydrogen ion secretion in the rabbit may in part have been induced by mineralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Third, urinary Pco2, even in sham controls receiving bicarbonate, was much lower in the previous study (53 mmHg) than that routinely observed in bicarbonate loaded control rats in our laboratory (100-120 mmHg) (14) (27). Compatible with our data, however, Robson et al (37) have reported that mineralocorticoid (9-afluorohydrocortisone) administration to adrenal intact rabbits increased the U-B Pco2 relative to controls undergoing a similar bicarbonate diuresis.…”
Section: Effects Ofcmasupporting
confidence: 63%
“…Third, urinary Pco2, even in sham controls receiving bicarbonate, was much lower in the previous study (53 mmHg) than that routinely observed in bicarbonate loaded control rats in our laboratory (100-120 mmHg) (14) (27). Compatible with our data, however, Robson et al (37) have reported that mineralocorticoid (9-afluorohydrocortisone) administration to adrenal intact rabbits increased the U-B Pco2 relative to controls undergoing a similar bicarbonate diuresis.…”
Section: Effects Ofcmasupporting
confidence: 63%
“…dog, and rat and has been interpreted as evidence of a deficit in distal (collecting duct) acidification in this herbivorous spe cies. Slightly or moderately increased (U-B)pC02 values have been measured in the alkaline urine of rabbits with 'normalized' serum levels of potassium [1], after oral a-9-fluorohydrocortisone [4] and after intrave nous furosemide [5]. Recently, Cruz-Soto et al [3] reported an increase in (U-B)pC02 in nonacidotic rabbits infused simultaneously with bicarbonate and acetazolamide.…”
Section: Introductionmentioning
confidence: 99%